Flourishing in French: promoting speaking skills in the Modern Foreign Language Classroom - Goldrick, R (2023)
This practitioner research study explores the effects of a focused intervention programme run across ten lessons with two Year 8 French classes (N=34) at a preparatory boarding school in the UK. The study seeks answers to the following research questions: 1. What, if any, is the effect of the focused intervention on the learners’ sense of flourishing? 2. What, if any, learner gains can be identified as a result of the focused intervention on speaking fluency? Baseline data were collected via speaking assessments and semi-structured student interviews. Following the intervention programme, data were collected again using speaking assessments, student questionnaires, and semi-structured student interviews. Findings identify a boosted sense of flourishing (self-efficacy, enjoyment, and confidence) and a range of learner gains in speaking fluency (phonological awareness, ambitious language, and spontaneity) in light of the intervention programme and across all three methods of data collection. Sampled speaking assessments (n=6) showed recording duration, pace (word and syllable), and overall marks have all increased by around one third post-intervention, indicating an improvement in speaking fluency. Results from student questionnaires (n=28) show that half of all students perceived improvements across all response categories. Almost all students perceived improvements in at least half of the response categories. Interviews revealed that, although students still have the tendency to experience emotions of worry, stress, or frustration when speaking in French, the intensity has decreased post-intervention.